Dissemination of solar power plant technology for household roofs - Ipniansyah Ipniansyah; Verra Aullia; Toyib Toyib (Universitas Muhammadiyah Magelang, 2021)
This Community Partnership Service Program (PKM) aims to provide science and technology solutions that are offered to community business groups in the Rapak Dalam Village, Loa Janan Ilir District, Samarinda City, East Kalimantan Province, namely in the form of Introduction to PLTS Roofing, Planning and Utilization of Rooftop PLTS. The method used in this PKM activity is socialization and assistance to the community. The results of achieving the targets include knowledge, understanding, and application of On Gid JTR - Rooftop PLTS, household community participation in preventing global warming, energy mix target of 23% by 2025; obtain the benefits of cost-effective PLN electricity (cheap electricity), meet human and environmental safety requirements, meet standards. The short-term category ranges from 60% to 70%, and the long-term category ranges from 90% to 99%. Components of PKM Activities and Variables Criteria for PKM Partners Business Groups as Household Consumers Using PLN Electricity and as PKM Business Groups Utilizing PLTS Roofs have been in accordance with the application of science and technology and meet applicable standards and regulations, where the qualitative level gains ranged from moderate to good, while the quantitative level is 70% to 90%.